Analysis of the overall development trends and hotspots in the research field of the human gut virome - Yidi Zhang; Ting Mei; Minhui Wang; Chunxia Huang; Hanzhi Yi; Yu Zhan; Sen Yang; Han Wang; Qiulong Yan; Ruochun Guo; Changming Chen (Virology Journal)
Abstract Background Dysbiosis of the human gut virome is associated with a variety of factors, yet the underlying mechanisms remain poorly understood. This study aims to map the current research trajectory of the human gut virome and propose a strategic framework for future scientific research. Methods A bibliometric analysis was performed on articles retrieved from the Web of Science (WoS) Core Collection database covering the period 2000 to 2024, utilizing VOSviewer, CiteSpace, and the R software environment. Results Over the past 20 years, the number of published papers and citations in the field of enterovirus research has shown a significant growth trend. This trend is attributed to the breakthrough progress of high-throughput sequencing technology and the iterative upgrade of viral genome databases such as CheckV, which has made the classification resolution of the enterovirus group more accurate and discovered a large number of unknown bacteriophages. Technological innovation has led to a fundamental transformation in the research model, evolving from the traditional single-virus species identification to the multi-omics integrated analysis of virus-host interaction networks. It is worth noting that the existing research shows a distinct feature of "imbalance between dry and wet experiments". Most of the achievements are based on bioinformatics analysis, while the translational medicine research involving virus isolation, culture and functional verification is still in its infancy (accounting for only 25%), especially the mechanism research evidence chain for key scientific issues such as the viral-host molecular interaction mechanism has not yet been completed. Conclusion The progress of enterovirus group research is developing rapidly. However, the species-level taxonomy of a large proportion of newly discovered bacteriophages remains unresolved. Future research must give priority to establishing a comprehensive functional database, and at the same time combine the systematic characterization of viral functions with the study of the mechanism of host-virus interaction to enable bacteriophages to play a role in maintaining human health.